Polymeric Display of Proteins through High Affinity Leucine Zipper Peptide Adaptors - Craig, Patricio Oliver (2012)
The polymeric display of proteins is a method that could be used to increase the immunogenicity of antigens and to enhance the interaction strength of binding domains for their target ligands through an avidity effect. However, the coupling of proteins to oligomeric scaffolds is challenging. The chemical conjugation and recombinant fusion techniques have limitations that prevent their general use. In this work we describe a simple and effective method for coupling proteins to the decameric structure of Brucella abortus Lumazine Synthase based on the use of a pair of high affinity heterodimeric coiled coil peptides complementary fused to the scaffold and the target protein. Results obtained with a series of proteins demonstrate the capability of this approach to generate polyvalent particles. Furthermore, we show that the method is able to increase the immunogenicity of antigens and produce polyfunctional particles with promising biomedical and nanotechnological applications.